Estudo da emissão de biogás em um aterro sanitário experimental - Juliana Goncalves Fernandes (2009)
Uncontrolled emissions of biogas is a serious problem of local and global air pollution. The effects of the release of gases locally vary from simple bad odor to possible carcinogenic diseases in the community surrounding the landfill. In relation to global air pollution and climate changes, the main effect of the release of biogas is the increasing of greenhouse effect. The main objective of this study is to evaluate the biogas emissions at the Experimental Sanitary Landfill in Belo Horizonte. Field tests, using static flux chamber device, were carried out in order to measure biogas emissions through the final cover. Gas emissions in 6 drains present in the experimental sanitary landfill have also been measured. The results obtained in field studies enabled the comparison with calculated values using the empirical method LANDGEM from USEPA. The experimental sanitary landfill has two final cover configurations. The first, called capillary barrier consisted of 30 cm soil overlaying 30 cm of recycled construction and demolition waste, and the second layer, called evapotranspirative cover, with about 60 cm of soil. The estimative of CH4 and CO2 average flow through the final cover using the methodology of flux chamber were 375 kg and 353 kg, respectively, released to the atmosphere per day. The procedures used to determine the gas flow in system of drains indicated very low values, suggesting a small efficiency of the drains. The results confirmed that the experimental sanitary landfill is at methanogenic phase with high concentration of CH4 and CO2. Comparing the internal concentration of methane to the emissions from the final cover, it was observed qualitatively a reduction of methane concentration between 38 and 68%. This fact dation of methane in the final cover layer due to presence of methanotrophic bacteria. Comparisons of values found using flux chamber to the values calculated by the model LANDGEM presented a large variation. These values were similar when extremes values of the parameters suggested by the model were used